Experimental evidence for the hydrothermal formation of native sulfur by synproportionation - Kürzinger, Victoria; Hansen, Christian T.; Strauss, Harald; Wu, Shijun; Bach, Wolfgang (Frontiers in Earth Science, 2023)
Elemental sulfur (S0) is known to form in submarine acid-sulfate vents by disproportionation of magmatic SO2. S0 formed upon disproportionation shows δ34SS values considerably lower than the influxing magmatic SO2, which results in δ34SS values typically < 0 ‰. The peculiar occurrence of isotopically heavy sulfur in the Kemp Caldera hydrothermal system (δ34SS > 5 ‰) and Niua North (δ34SS = 3.1 ‰) led to the suggestion that disproportionation is not the only sulfur forming process in submarine hydrothermal systems. We conducted hydrothermal experiments to investigate if synproportionation of SO2 and H2S can explain the occurrence and isotopic composition of S0 observed in some vent fields. Provided that SO2 and H2S are both abundant, this formation mechanism is thermodynamically conceivable, but it has not yet been demonstrated experimentally that this process actually takes place in submarine hydrothermal systems. We conducted the experiments in collapsible Ti-cells under pT-conditions (20–30 MPa, 220 °C) that are relevant to S0 formation in submarine hydrothermal systems. We used starting concentrations of 10 mM sulfite and 20 mM sulfide of known isotopic composition. Under acidic conditions (pH25 °C = 1.2), S0 was the most abundant reaction product, but small amounts of sulfate were also produced. A Rayleigh fractionation model was applied to determine the isotopic composition of SO42–, SO2, H2S and S0 expected to form by SO2 disproportionation, H2S oxidation, and SO2–H2S synproportionation. The sulfur isotopic signatures of the sulfur produced in the experiments can only be explained by synproportionation of sulfite and sulfide. These results provide strong evidence that synproportionation is likely responsible for exceptionally high δ34SS values observed in S0 from some arc/back-arc hydrothermal environments, like the Kemp Caldera in the South Sandwich arc. Coeval degassing of H2S and SO2 is likely required to have this particular reaction dominate in the H-S-O reaction network and produce noticeable accumulations of isotopically heavy native sulfur at the seafloor.